PEMANFAATAN MEDIA SOSIAL UNTUK MEMASARKAN DESTINASI KOLAM PANCING PADA DESA GUNUNGSARI GEMPOL - Joshua, Joshua; Kh, Nur Sitti; EDS, Efi; Freida, Freida; Yunus, Yudi; Syafik, Ali; Andhini, Andhini; Fajarul, A; Syafi, Al (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service aims to activate the potential of the village, which is currently limited due to a lack of resources. Although there is land available, necessary resources are still insufficient. The Initial activity conducted was a socialization event to highlight the importance of marketing, particularly through social media. To improve the area around the fishing pnd, landscaping was carried out to make it look more organized. Additionallly directional signs were created to facilitate access, considering the numerous routes leading to the pond. A video was produced, showcasing the route from the village entrance to the fishing pond with the hope that it will help visitors find the location easily. Moreover it is expected that not only the fishing pond can generate income for the village, but also the kiosks present. This initiative aims to boost the local economy and promote the development of small and medium sized enterprisis (UMKM) in the village.